The Impact of Spatial Layout on Commercial Property Value - Feliandi, Richard; Sitanggang, Yosephine (Jurnal Arsitektur, 2025)
Tangerang regency has an extensive administrative area, which makes some residential areas are closer to the government center of another city, such as Tangerang city. One example is Villa Tomang Baru residential area. Despite its strategic location and supporting facilities, it has a commercial area called Tomang Baru Square that lacks visitors and tenants. Therefore, the purpose of the paper is to analyse the impact of commercial space layout on property value in Tomang Baru Square. The analysis was carried out with a qualitative method by collecting observation data and doing literature studies. From the literature study, the author found several research parameters for the spatial layout variable and the property value variable. Literature findings show that property value can be analyzed through four aspects: utility, scarcity, effective demand, and transferability. Meanwhile, spatial layout is assessed based on the presence of anchors, supporting activities, integration and accessibility, building visuals, and comfort and security. Based on the analysis result, it was found that the utility, effective demand, and transferability aspects were still not being fulfilled and therefore the property value has decreased.